Shaking Table Test of a RC Frame with EPSC Latticed Concrete Infill Wall - Baizan Tang; Xiaojun Li; Su Chen; Lihong Xiong (Shock and Vibration)
The expansive polystyrene granule cement (EPSC) latticed concrete wall is a new type of energy-saving wall material with load-bearing, insulation, fireproof, and environmental protection characteristics. A series of shaking table tests were performed to investigate the seismic behavior of a full-scale reinforced concrete (RC) frame with EPSC latticed concrete infill wall, and data obtained from the shaking table test were analyzed. The experimental results indicate that the designed RC frame with EPSC latticed concrete infill wall has satisfactory seismic performance subjected to earthquakes, and the seismic responses of the model structure are more sensitive to input motions with more high frequency components and long duration. The EPSC latticed concrete infill wall provided high lateral stiffness so that the walls can be equivalent to a RC shear wall. The horizontal and vertical rebar, arranged in the concrete lattice beam and column, could effectively restrain the latticed concrete infill wall and RC frame. To achieve a more comprehensive evaluation on the performance of the RC frame with latticed concrete infill walls, further research on its seismic responses is expected by comparing with conventional infill walls and nonlinear analytical method.